Calibration and evaluation of the Lemaitre damage model using axial- torsion fatigue tests on five engineering alloys - Castro, Fábio (2018)
The Lemaitre damage model is evaluated using fatigue test data from five engineering alloys: 1045 steel, 16MnR steel, 7075-T651 Al alloy, extruded AZ61A Mg alloy, and extruded AZ31B Mg alloy. Tension-compression, torsion, proportional axial-torsion, and 90° out-of-phase axial-torsion loadings were investigated. The results show that the overall accuracy of the fatigue life estimates made by using the Lemaitre model is comparable to those obtained by fatigue models that require the definition of a loading cycle. A simple and effective method is described for determining the material constants of the Lemaitre model.